Model Implementasi Pendidikan Nilai Karakter Profil Pelajar Pancasila di Kelas Empat Sekolah Dasar - Yusup, Muhamad; Sumantri, Mohamad Syarif; Lestari, Ika (Jayapangus Press, 2024)
The aim of this research is to describe the implementation model of the independent curriculum at the SDIT Irsyadul 'Ibad School, Pandeglang Regency as a school driving the first generation in forming the character profile of Pancasila students. This research method is descriptive qualitative. Data was collected through interviews with school principals, deputy principals, teachers and parents. Data was obtained from documentation, observation and literature study. The data obtained is then analyzed through reduction, presentation and conclusions. The research results showed that the implementation of the Pancasila student profile character was not only through intracurricular, extracurricular activities and the Pancasila Student Profile Strengthening Project but also through school habits/culture. Apart from that, the success of implementing the Pancasila student profile character is influenced by the creativity and competence of teachers in differentiated learning as well as the absolute prohibition of smoking for teachers. Schools have the freedom to prepare learning plans that refer to learning outcomes based on student characteristics. Collaboration between school principals, teachers, students, parents and the community is an important factor in implementing the independent curriculum.